(untitled) (Bulletin of criminological association of Ukraine, 2023)
It was established that in the leading democratic states of the world, forests and forest resources belong to the circle of the most important national values, which have significant economic, social and cultural significance. For the proper preservation and restoration of these values, multi-level power mechanisms of forestry management have been introduced in foreign countries, which include supervision and control over the protection, protection, use and reproduction of forests. It is emphasized that in most leading countries, the effectiveness and completeness of supervision and control in the field of forestry is achieved due to a comprehensive approach to solving this issue, which is expressed, first of all, in the fact that control measures are carried out by public authorities specializing in issues of forestry, as well as bodies and services on issues of environmental safety. At the same time, special subjects on forestry issues and subjects of environmental supervision and control can belong to the vertical of either one ministry (as a rule, this is the ministry that takes care of ecology and nature protection issues), or to different departments (for example, in a number of countries, forest control services are subordinated to the ministries of agriculture, and eco-control services are subordinated to the ministries of ecology and nature protection, respectively.